Passive sampling of perfluorinated acids and sulfonates using polar organic chemical integrative samplers - Fedorova, Ganna; Golovko, Oksana; Randak, Tomas; Grabic, Roman (Environmental science and pollution research international, 2013)
The applicability of a polar organic chemical integrative sampler (POCIS) for detection and determination of perfluorinated acids and sulfonates in water was studied under field conditions. Standard POCIS configurations (i.e., pharmaceutical and pesticide) were deployed in effluent from a wastewater treatment plant for 1, 2, and 3 weeks. Ten of 15 target compounds were found in POCIS, five of which were quantified in wastewater. Pest-POCIS appeared more effective for the sampling, while Pharm-POCIS had a more rapid uptake kinetic, which leads to faster saturation or equilibrium. The results showed that the pesticide configuration is probably more suitable for the sampling of this class of compounds. Based on average concentration in water over the sampling period and amount of compound adsorbed in the POCIS, we calculated sampling rates for five studied compounds and obtained values of 0.034 to 0.222 L day(-1).
Keywords: chemické látky znečišťující vodu; polymery; Polymers; Wastewater; Water Pollutants, Chemical; monitorování životního prostředí; plynová chromatografie s hmotnostně spektrometrickou detekcí; Alkanesulfonates; odpadní voda; Gas Chromatography-Mass Spectrometry; Environmental Monitoring; Fluorocarbons; alkylsulfonany; fluorokarbony